Cybersecurity Challenges and Investment in Indonesia - Purwandari, Nuraini (Indonesian Scientific Publication, 2024)
Indonesia’s digital economy has expanded rapidly, but this growth has been accompanied by a sharp rise in cyber threats, particularly ransomware and phishing attacks. Despite this, national cybersecurity investment remains critically low, at just 0.02% of GDP—among the lowest in ASEAN. This study analyzes the structural misalignment between the increasing threat landscape and the country’s financial and policy responses. Using secondary data from 2020 to 2023, it examines attack frequencies, regional investment comparisons, and projected market growth. Key results indicate that while cyber incidents have escalated—from 88 million in early 2020 to 347 million in H1 2023—Indonesia's cybersecurity market is projected to grow from USD 1.07 billion in 2024 to USD 3.48 billion in 2030. However, regulatory fragmentation, limited SME readiness, and underdeveloped public-private coordination remain significant barriers. The study concludes that addressing policy fragmentation, increasing investment, and integrating SMEs into the national strategy are essential to secure Indonesia’s digital future and unlock the potential of its growing cybersecurity market.